Territorial games : understanding and ending turf wars at work - Simmons, Annette (New York : AMCOM, 1998)
Territorial games are the unfortunate reality of the workplace, says behavioral scientist and corporate peacemaker Annette Simmons in this provocative and practical book. But the good news is that these instinctual games are more like bad habits than entrenched, compulsive behaviors. And bad habits can be changed. Territorial Games explains what emotions are driving the behaviors and how to recognize which game is being played. It supplies real-life scenarios that further clarify the behaviors and self-tests to uncover your own predilection for playing each game. And, best of all, Territorial Games supplies positive strategies for combating workplace turf wars.
Pt. 1. Understanding the Impulse Behind Territorial Behavior. 1. Genius Into Gruel. 2. Why Smart People Play Stupid Games. 3. The Line of Diminishing Returns -- Pt. 2. Ten Territorial Games. 4. The Occupation Game. 5. The Information Manipulation Game. 6. The Intimidation Game. 7. The Powerful Alliances Game. 8. The Invisible Wall Game. 9. The Strategic Noncompliance Game. 10. The Discredit Game. 11. The Shunning Game. 12. The Camouflage Game. 13. The Filibuster Game. 14. Serious Sabotage --Pt. 3. Ending Turf Wars. 15. Tearing Down the Walls. 16. Ripping Up the Foundations. 17. Building a New Map. 18. Playing New Games.
Includes bibliographical references (p. 219-220) and index.
Keywords: Personnel management; Interpersonal relations; Human territoriality